Analisis Model Kooperatif Dalam Pembelajaran Blended Learning Statistika: (STAD dan Jigsaw) - Riska Yulianti; Luluk Wahyu Nengsih; Asep Rosadi (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
This research is an experimental study that aims to determine the difference in learning outcomes between students who are taught using the STAD cooperative learning model and those who are taught using the Jigsaw cooperative learning model. The population in this study was all students in class XI SMK Negeri 2 Jayapura for the academic year 2021â€“2022, totaling 111 people. The sample was taken using a purposive sampling technique, totaling 51 people, consisting of two classes, namely class XI, Office 3, and Class XI, Office 4. Class XI Office 3 (experimental class) is a class that is taught using the STAD cooperative learning model, and Class XI Office 4 (control class) is a class that is taught using the Jigsaw cooperative learning model.Â The obtained data were then analyzed using parametric statistics via a t-test. The results showed that: 1) there was no significant difference in mathematics learning outcomes between students taught by the STAD type of cooperative learning model and students who were taught by the Jigsaw type of cooperative learning model; 2) the mean of mathematics learning outcomes of students who are taught the STAD type of cooperative learning model is lower than that of students who are taught the JIGSAW type of cooperative learning model, which is 62.61 smaller than 70.43.Keywords: Cooperative model, Blended learning, Statistics